THE REFINANCING BALANCE SHEET. - Himmelbla, David (The Accounting Review, 1927)
A condensed balance sheet which reflects all the adjustments arising from and incidental to the proposed financing is often used in the circular issued by the banker, when offering securities for sale. The adjustments fall into three main groups: new funds obtained from-bonds or notes to lie sold; stock to be sold; assets to be liquidated; new funds to be disposed of-to retire funded debt; to retire certain issues of preferred stock; to liquidate short-term debt; for additions to plant, by withdrawal of cash or other assets from the business; internal readjustments-reclassification of capital stock issues; revaluation of assets, stock dividend; etc. The cost of the new financing is usually included in deferred charges and the excess of the funds obtained over funds to be expended is included in the cash item. A matter of importance in constructing and handling special statements is that of interim changes in conditions. It is essential that the auditor examine the accounts for these intervening months to ascertain that nothing transpired during that period which affects adversely the company's financial condition. It is also important that the statement reflect as nearly as may be the prospective financial condition after the financing is consummated.